A simple single bounding surface model for undrained cyclic behaviours of saturated clays and its numerical implementation. Issue 139 (December 2020) - Cheng, Xinglei; Du, Xiuli; Lu, Dechun; Ma, Chao; Wang, Piguang
Abstract: A simple single bounding surface constitutive model is developed to predict the undrained behaviours of saturated clays under cyclic loads. The new model does not involve complex kinematic hardening rules, and it is only required to memorize important stress reverse events; therefore, the simplicity should be the largest advantage of the model. A new interpolation function of an elastoplastic shear modulus is proposed based on bounding surface theories. The evolution of a hardening modulus is described in the deviatoric stress space by the movement and updating of a mapping centre based on the new interpolation function, which enables the model to describe the stress-strain hysteretic responses of clays under cyclic loading. The new model can be regarded as an improvement of some classical one-dimensional soil dynamic models and a generalization in three-dimensional stress space. The model parameters can usually be determined by performing triaxial tests. The model performance has been verified by a comparative analysis on clays subjected to one-way and two-way cyclic loading at different stress levels. The developed model can capture the essential features of behaviours in saturated clay, including reverse plastic flow, evolution of hysteretic loops, accumulation of plastic deformations and soil stiffness degradation. The newly developed constitutive model has been successfully encoded into the ABAQUS software package by the secondary development interface of UMAT. The ability of the model to calculate boundary value problems, such as clay foundations subjected to seismic loads, has been verified to some extent by simulating the seismic responses of homogeneous horizontal sites. Highlights: A simple single bounding surface model was developed to predict undrained cyclic behaviors of clays. The new model can capture the reverse plastic flow and the soil stiffness degradation. The new model has been successfully encoded into ABAQUS software. Ability of the model to calculate responses of clay foundations under seismic loads was verified.